A communities Eden – grazing Exclosure success in Ethiopia. Issue 5 (3rd September 2017) - Rossiter, John; Wondie Minale, Markos; Andarge, Workneh; Twomlow, Stephen
ABSTRACT: The traditional significance of livestock to rural communities in Ethiopia has resulted in intense pressures on available grazing areas, resulting in vegetation loss, reduced infiltration and increased runoff, greater erosion and land degradation. Unfortunately, the uptake of sustainable land management (SLM) practices in communal grazing land is constrained by a lack of land tenure security. Recently the International Fund for Agricultural Development, working with the Government of Ethiopia, has invested in the capacity of local administrations, to improve land demarcation and the issuance of both individual and community land certificates. This is concurrent with the promotion of improved SLM, particularly zero grazing of communal lands, known by communities as Exclosures. This pilot study reports the biophysical changes observed in four different Exclosures in the Amhara region compared to adjacent communal lands. Irrespective of age, it was found that vegetative cover, biodiversity levels and infiltration rates, all increased in Exclosures, enhancing ecosystem services and function. Results suggest that Exclosures are most effective for large sites with effective cut and carry forage systems. It is evident that the issuance of land titles increases the adoption of SLM practices. Further studies are required to assess the economic and social impacts of Exclosures.